Optimizing Restless Legs Syndrome Care: Integrating Rehabilitation into Multimodal Management - Umer Younas; Muhammad Tawab Khalil; Hafsa Abdul Qadir; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2025)
Restless leg syndrome (RLS) is a common yet frequently under-diagnosed condition. The exact pathophysiology is unknown, however multiple factors including genetic factors, brain iron deficiency and dysfunction of dopaminergic system are associated with RLS. It is a clinical diagnosis confirmed by International Restless Legs Syndrome Study Group (IRLSSG) consensus diagnostic criteria (2012). Several pharmacological and non - pharmacological management options are available for treatment of RLS. Non-pharmacological management options include lifestyle modifications, therapeutic exercises (aerobic training, resistance training and flexibility exercises), physical modalities (pneumatic compression, vibration therapy, and near-infrared light) and mind body approaches (yoga, cognitive behavioural therapy, acupuncture, massage, and mindfulness). Pharmacological management of RLS include drugs from various classes including gabapentinoids, dopamine agonists, opioids and iron therapy. Novel treatment options like peroneal nerve stimulation, botulinum toxin injection, transcranial magnetic stimulation, vagus nerve stimulation, spinal cord stimulation and deep brain stimulation are still in experimental phase. Keywords: Deep Brain Stimulation; Vagus Nerve Stimulation; Gabapentin; Anemia, Iron-Deficiency; Acupuncture